Network pharmacology integrated with experimental validation to explore the therapeutic role and potential mechanism of Epimedium for spinal cord injury - Fu, Xuanhao; Ma, Boyuan; Zhou, Mengmeng; Cheng, Yuelin; Liu, Linyan; Kan, Shunli; Liu, Chengjiang; Zhao, Xinyan; Feng, Sa; Zhu, Haoqiang; Hu, Wei; Jiang, Zehua; et al. (Frontiers in Molecular Neuroscience, 2023)
Objective Epimedium (EPI) is a common Chinese herb with neuroprotective effects against a variety of central nervous system disorders, especially spinal cord injury (SCI). In this study, we performed network pharmacology and molecular docking analyses to reveal the mechanism underlying EPI treatment of SCI, then validated its efficacy using animal models. Methods The active ingredients and targets of EPI were screened by Traditional Chinese Medicine Systems Pharmacology (TCMSP) and their targets annotated on the UniProt platform. SCI-related targets were searched from OMIM, TTD, and GeneCards databases. We employed the STRING platform to construct a protein–protein interaction (PPI) network then visualized the results using Cytoscape (3.8.2) software. We also subjected key EPI targets to ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses, then docked the main active ingredients with the key targets. Finally, we established an SCI rat model to evaluate efficacy of EPI in treating SCI and validate the effects of different biofunctional modules predicted by network pharmacology. Results A total of 133 EPI targets were associated with SCI. GO terms and KEGG pathway enrichment results showed that EPI’s effect in treating SCI was significantly associated with inflammatory response, oxidative stress and the PI3K/AKT signaling pathway. Molecular docking results indicated that EPI’s active ingredients have a high affinity for the key targets. Results from animal experiments revealed that EPI not only markedly improved Basso, Beattie, and Bresnahan scores in SCI rats, but also significantly improved p-PI3K/PI3K and p-AKT/AKT ratio. Moreover, EPI treatment not only mediated a significant decrease in malondialdehyde (MDA) but also increased both superoxide dismutase (SOD), and glutathione (GSH). However, this phenomenon was successfully reversed by LY294002, a PI3K inhibitor. Conclusion EPI improves behavioral performance in SCI rats through anti-oxidative stress, which may be mediated by activation of the PI3K/AKT signaling pathway.